2017
DOI: 10.1080/0284186x.2016.1266083
|View full text |Cite
|
Sign up to set email alerts
|

Sustained employability and health-related quality of life in cancer survivors up to four years after diagnosis

Abstract: Background: Most cancer survivors are able to return to work at some point after diagnosis. However, literature on sustained employability and health-related quality of life (HRQoL) is limited. Therefore, the aims of this study were to explore the influence of change in employment status on HRQoL in cancer survivors long term after diagnosis, and to identify predictors of work continuation in occupationally active survivors. Material and methods: We used prospective data (T0 ¼ two years after diagnosis, T1 ¼ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 33 publications
7
71
0
Order By: Relevance
“…This study showed no association between cancer site and cancer treatment with any work functioning trajectory. Recently, Duijts et al . also found no differences in cancer site and treatment for cancer patients who are “continuously working” or “not‐continuously working” 4 years after diagnosis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This study showed no association between cancer site and cancer treatment with any work functioning trajectory. Recently, Duijts et al . also found no differences in cancer site and treatment for cancer patients who are “continuously working” or “not‐continuously working” 4 years after diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have addressed the employment consequences of cancer survivorship in terms of employment status . A recent study in occupationally active cancer patients up to four years after diagnosis showed that good work ability was associated with work continuation . An in‐depth review by Munir et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, survivors who had stopped working after the initiation of treatment cited these benefits as reasons for contemplating a return to work. Positive associations between employment, quality of life, self‐esteem, and satisfaction have been shown among cancer survivors . Swanberg et al found that survivors of breast cancer reported a sense of responsibility that included the need for normalcy as an influential reason for continued employment throughout cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This led to a shift from merely focusing on survival to also focusing on short‐term effects, and long‐term effects as well as late effects of cancer and its treatment. For cancer survivors of working age, inability to return to work or continue working is one of these late effects that can negatively impact their quality of life (Duijts, Kieffer, van Muijen, & van der Beek, ). That is, because work gives them, for instance, a feeling of contributing to society (Tiedtke, de Rijk, Dierckx de Casterle, Christiaens, & Donceel, ), and as work provides them a much‐needed income (Yabroff et al, ).…”
Section: Introductionmentioning
confidence: 99%